Development of LCDS-Based Interactive Electronic School Book on Blackbody Radiation as Self-Instructional Materials for Fostering Student’s Critical Thinking - Ayuningtias, Meta Dwi; Suyatna, Agus; Suyanto, Eko; Nwineh, Legborsi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
This study aims to develop an LCDS- based the interactive electronic school book on blackbody radiation that is valid as self-instructional materials to foster students' critical thinking skills. The method used was research and development. The stages of the research were determining the existing potentials and problems, information gathering, product design, product validation, the final revision of the product, and feasibility tests and practicality of operation. The research instrument used was a questionnaire. Interactive electronic school book has supporting contents, namely user manual, user learning process, video, animation, simulations, and interactive tests. Expert test for product consists of content validation with the score of 3,36 (very appropriate) and design validation with the score of 3,45 (very appropriate). Readability of LCDS- based interactive electronic school book on blackbody radiation got the score of 3, 23 which belongs to the good quality. The practicality aspects got a score of 3.28 which means it can be operated independently